2019
DOI: 10.1021/acs.jpclett.9b02802
|View full text |Cite
|
Sign up to set email alerts
|

How Surfactants Affect Droplet Wetting on Hydrophobic Microstructures

Abstract: Surfactants, as amphiphilic molecules, adsorb easily at interfaces and can detrimentally destroy the useful, gas-trapping wetting state (Cassie−Baxter, CB) of a drop on superhydrophobic surfaces. Here, we provide a quantitative understanding of how surfactants alter the wetting state and contact angle of aqueous drops on hydrophobic microstructures of different roughness (r) and solid fraction (ϕ). Experimentally, at low surfactant concentrations (C), some drops attain a homogeneous wetting state (Wenzel, W), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 60 publications
(98 reference statements)
0
26
0
Order By: Relevance
“…This significant increase in the wetting area leads to the replacement of the insulating air pockets existing on the superhydrophobic coatings by liquid 35 and transition of the wetting state of the droplet from Cassie− Baxter to Wenzel. 52 Consequently, by replacing the insulating air pockets with liquid, which results in an increase in thermal conductivity as well as enhancement of the solid−liquid interfacial area, freezing is accelerated in the SDS solutions. To put it briefly, the energetic barrier for ice nucleation of SDS solutions on the superhydrophobic coatings is reduced at subzero temperatures of −20 and −30 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant increase in the wetting area leads to the replacement of the insulating air pockets existing on the superhydrophobic coatings by liquid 35 and transition of the wetting state of the droplet from Cassie− Baxter to Wenzel. 52 Consequently, by replacing the insulating air pockets with liquid, which results in an increase in thermal conductivity as well as enhancement of the solid−liquid interfacial area, freezing is accelerated in the SDS solutions. To put it briefly, the energetic barrier for ice nucleation of SDS solutions on the superhydrophobic coatings is reduced at subzero temperatures of −20 and −30 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the previous sections, it was shown that regardless of the concentration, SDS droplets easily spread on the substrate, inhibit the retraction, and enhance the droplets relaxing diameter (Figure ). This significant increase in the wetting area leads to the replacement of the insulating air pockets existing on the superhydrophobic coatings by liquid and transition of the wetting state of the droplet from Cassie–Baxter to Wenzel . Consequently, by replacing the insulating air pockets with liquid, which results in an increase in thermal conductivity as well as enhancement of the solid–liquid interfacial area, freezing is accelerated in the SDS solutions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the modified CB eq 6 well predicted C S -dependent CA for CB drops, it does not explain the probability and the stability of the wetting states (shown in Figure 2). To get a better understanding concerning the stability and the metastability of the observed wetting behavior and to explain the occurrence of different wetting states depending on the C S on the different microstructures, we carried out an analysis starting from the Gibbsian thermodynamics, 23,38,53−57 following the work by Shardt et al 38 using SDS surfactants, and analytically estimated the free energy (E) for our composite system of DDAB-laden surfactant droplets sitting on a microstructured surface. The derived free-energy equation, E − E 0 , with respect to the assumed reference state has the form of Shardt et al 38 free energy…”
Section: Modified W and Cb Ca Equationsmentioning
confidence: 99%
“…We followed a model that a droplet transiting from the CB to W wetting state usually occurs through two main phases as described below. 23,38,58 In this first phase, after droplet deposition, the liquid is falling down along the pillars with an assumed flat LV interface as in the CB wetting state (with f = ϕ and f 1 = 1 − ϕ), until it wets the bottom of the surface. Here, we assume that only the cylinder's walls are wet and the bottom surface is not wet, so f increases and f 1 = 1 − f. At the end of the first phase, the value of f further increases as the solid−liquid contact area increases.…”
Section: Modified W and Cb Ca Equationsmentioning
confidence: 99%
“…The gas-trapping CB wetting state, contributing to a large contact angle and a low CA hysteresis, is critical to resilient superhydrophobicity, which is beneficial for various applications in surface engineering. However, the long-term stability of the preferred CB state on SH surfaces is still challenging and can be lost through an irreversible wetting transition to Wenzel state, when exposed to a high-temperature environment, droplet evaporation, , or surfactant additives. …”
Section: Introductionmentioning
confidence: 99%